Asymptomatic Solitary Metastasis to the Testis From Prostate Carcinoma Detected by FDG PET/CT. (January 2016) - Hsieh, Te-Chun; Lin, Ching-Chan; Kao, Chia-Hung; Wu, Yu-Chin; Sun, Shung-Shung
Abstract : Abstract: Testicular metastases, despite their proximity, from prostate adenocarcinoma are rare and usually found along with bone or other visceral metastases. We herein present a case with recurrent disease of prostate adenocarcinoma as solitary testicular metastasis detected by 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT).